Hegel's logical determinations. - Frias, Denis. (University of Ottawa (Canada), 1999)
The system of logical determinations outlined in Hegel's Science of Logic is capable of further development because it is an aspect of a living process called the Idea. The system does not develop by the addition of new categories of thought, rather it develops when philosophers achieve insights into the nuances in the ways the logical determinations interrelate. Philosophers attain this nuanced knowledge by witnessing the process at work, and by actively analyzing the various experiential events occurring around them.
Keywords: Philosophy.